The efficacy and safety of dapagliflozin in pediatric heart failure: Interpreting causality in clinical outcomes - Kaiyuan Cena; Fatimah Ahmedy; Mexmollen Marcus; Mohd Fadzli Shukor (Elsevier B.V., 2025)
We read with great interest the report by Kumar et al. [1], which describes functional and echocardiographic improvements in pediatric heart failure after initiating dapagliflozin. These encouraging findings offer valuable insights; however, attributing the clinical benefits solely to the drug may be premature given certain limitations in study design and interpretation. In observational analyses—especially in cohorts with diverse characteristics—multiple factors can contribute to the outcomes observed.